Aplikasi Penjualan Online Berbasis Android (Studi Kasus: Di Toko Hoax Merch ) - Marjito Marjito; Gina Tesaria (Jurnal Computech & Bisnis (e-Journal), 2016)
The development of e commerce in Indonesia is increasing rapidly, it requires businesses to be able to adapt to adopt online sales. One of the largest platform currently used by internet users is the android. The purpose of this study to create an online sales application. Advances in technology requires that the company can adapt to these advancements, it is intended to simplify the business processes. This research is expected to help the company in order to facilitate the sale transaction with Android based.  Keywords: online sales; android.